Preparation method and application of self-supporting Ru / Ni-MOF electrocatalyst
By constructing a self-supported Ru/Ni-MOF electrocatalyst, and dispersing atomic-scale Ru into the Ni-MOF structure using an ion exchange strategy, the problems of high prices and poor stability of precious metal catalysts in the prior art are solved, and efficient and stable hydrogen evolution reactions and the effect of reducing production costs are achieved.
Patent Information
- Application Number
- CN202510062973.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing electrolytic hydrogen production technology, commercial precious metal Pt-based catalysts are expensive, which is not conducive to industrial application. In addition, traditional powder catalysts are prone to fall off during the preparation of electrodes, affecting stability.
By constructing a self-supported Ru/Ni-MOF electrocatalyst, atomic-scale Ru is uniformly dispersed into the Ni-MOF structure using an ion exchange strategy to form a high-performance self-supported hydrogen evolution electrode.
A high-efficiency hydrogen evolution reaction is achieved, which significantly improves catalytic performance and stability, reduces production costs, and simplifies the electrode preparation process.
Smart Images

Figure CN119710819A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technology of preparing electrocatalysts used in the field of hydrogen production by electrolysis of water, and specifically relates to the preparation and application of a self-supporting Ru / Ni-MOF electrocatalyst. Background Art
[0002] The development of green and clean energy is crucial to alleviating the energy crisis and improving the increasingly serious environmental problems. Hydrogen energy, as a zero-carbon, high-energy-density clean energy, will occupy an important position in the future green energy structure. Water electrolysis hydrogen production technology has the advantages of high hydrogen purity and pollution-free reaction, and is one of the most promising hydrogen production technologies. As one of the half-reactions of water electrolysis hydrogen production, the hydrogen evolution reaction requires an efficient electrocatalyst to reduce the reaction energy barrier and reduce electricity consumption. The current commercial precious metal Pt-based catalysts are expensive, which is not conducive to industrial applications. Therefore, it is necessary to seek low-cost and highly active electrocatalysts to improve the efficiency of hydrogen production.
[0003] Metal-organic framework (MOF) is an emerging type of porous crystalline material with advantages such as adjustable structure and large specific surface area. By selecting the appropriate metal center and organic ligand type, it has shown great application prospects in the field of energy storage and conversion. The cost of the precious metal Ru is lower than that of Pt, but the metal hydrogen bond strength of Ru is similar to that of Pt. By dispersing atomic-level dispersed Ru into the MOF framework, the unique advantages of the two can be fully utilized, the activity and stability of the catalytic hydrogen evolution reaction can be enhanced, and the effect of double-atom synergistic catalysis can be achieved. At the same time, atomic-level dispersed Ru can improve the atomic utilization efficiency and reduce the production cost of the catalyst. In the process of preparing electrodes, the addition of binders to traditional powder catalysts will bury some active sites and easily fall off from the electrode surface, affecting stability. Growing the catalyst in situ on the substrate surface to construct a self-supporting electrode can fully expose the active sites, enhance the stability of the catalyst, and is expected to achieve industrial application. Therefore, it is of great research significance to evenly disperse atomic-level dispersed Ru in the MOF structure and construct a high-performance self-supporting hydrogen evolution electrode to achieve high-efficiency hydrogen production. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to construct a self-supporting two-dimensional Ni-MOF nanosheet array and provide a preparation method for dispersing atomic-level Ru into the MOF structure using an ion exchange strategy, thereby obtaining a self-supporting hydrogen evolution electrode with excellent activity and stability.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions.
[0006] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Cleaning of nickel foam substrate; (2) dissolving the metal nickel salt and the carboxylic acid organic ligand in N,N-dimethylformamide (DMF) and distilled water under stirring conditions, pouring the stirred mixed solution into a high-pressure reactor, and adding the clean nickel foam in step (1). After a specific time of solvent thermal reaction under certain temperature conditions, the temperature is cooled to room temperature, and the nickel foam on which MOF is grown is taken out, rinsed with distilled water and ethanol for multiple times, and freeze-dried to obtain a two-dimensional Ni-MOF nanosheet array grown on the nickel foam substrate; (3) Ruthenium chloride is added to an alcohol solvent and ultrasonically stirred for 5 minutes to form a uniform solution. The solution is then transferred to a high-pressure reactor and the nickel foam on which Ni-MOF is grown is placed. The solution is heated at a constant temperature in an oven for ion exchange so that atomic-level Ru is evenly dispersed in the MOF structure. After the reaction, the solution is rinsed with ethanol and distilled water for multiple times, and freeze-dried to obtain a self-supporting Ru / Ni-MOF nanomaterial.
[0007] Furthermore, in step (1): the nickel foam is sequentially placed in a 2M dilute hydrochloric acid solution, distilled water and ethanol and ultrasonically cleaned for 5-10 minutes respectively to remove the oxide layer and organic impurities on the surface of the substrate.
[0008] Furthermore, in step (2), the metal nickel salt is one of nickel chloride or nickel nitrate, and the organic ligand is 2,6-naphthalene dicarboxylic acid.
[0009] Preferably, in step (2), the molar ratio of nickel salt to 2,6-naphthalene dicarboxylic acid ligand is 1:1-1:3; further specifically selected are 1:1, 1:2, 1:3.
[0010] The volume ratio of DMF to distilled water in step (2) is 6:1-10:1, and is further specifically selected to be 6:1, 8:1 and 10:1.
[0011] The solvent thermal reaction temperature in step (2) is 100-160°C, and more specifically 110°C, 130°C and 160°C; the reaction time is 8-16h, and more specifically 8h, 12h and 16h.
[0012] Furthermore, in step (3), the alcohol solvent is one of methanol or ethanol.
[0013] Preferably, in step (3), the mass of ruthenium chloride is 0.02 g-0.04 g, and more specifically 0.02 g, 0.03 g or 0.04 g; the volume of ethanol is 20-40 mL, and more specifically 20 mL, 30 mL or 40 mL.
[0014] In step (3), the ion exchange temperature is 60-100°C, more specifically 70°C, 80°C or 100°C; the reaction time is 10-16h, more specifically 10h, 12h or 16h.
[0015] The present invention also provides an application of a self-supporting Ru / Ni-MOF electrocatalyst in a hydrogen evolution reaction. The self-supporting Ru / Ni-MOF electrode can be directly used as a working electrode for the hydrogen evolution reaction, showing excellent catalytic activity and long-term stability.
[0016] Beneficial technical effects of the present invention: (1) Compared with the prior art, the preparation method of the present invention is easy to implement and has good reproducibility. The obtained ultra-thin two-dimensional MOF array can fully expose the active sites.
[0017] (2) Atomic-level Ru is dispersed into the Ni-MOF structure through an ion exchange strategy. This method is simple to operate and is conducive to industrial production. In addition, the highly dispersed Ru atoms can improve the utilization efficiency of precious metal atoms and reduce costs.
[0018] (3) The Ru / Ni-MOF electrocatalyst constructed by the present invention has a synergistic effect between Ni and Ru atoms, which significantly improves the hydrogen evolution catalytic performance. The obtained Ru / Ni-MOF self-supporting nanoarray simplifies the electrode preparation process and can be directly used as a working electrode, avoiding the addition of a binder to bury the active sites, thereby increasing long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The diffraction patterns of Ni-MOF and Ru / Ni-MOF powders prepared in Example 1 of the present invention.
[0020] Figure 2 Scanning electron microscope images of Ni-MOF and Ru / Ni-MOF prepared in Example 1 of the present invention.
[0021] Figure 3 This is an atomic force microscope image of the Ru / Ni-MOF prepared in Example 1 of the present invention.
[0022] Figure 4 This is a transmission electron microscopy image of the Ru / Ni-MOF prepared in Example 1 of the present invention.
[0023] Figure 5 Polarization curves of the self-supporting Ni-MOF and Ru / Ni-MOF prepared in Example 1 of the present invention as working electrodes for hydrogen evolution reaction.
[0024] Figure 6This is a long-term stability test chart of the self-supporting Ru / Ni-MOF catalyzed hydrogen evolution reaction prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited to the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0026] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0027] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 24mL DMF and 3mL distilled water, and dissolve them by ultrasonic. Pour the mixed solution into a 50mL reactor, add the cleaned nickel foam, and carry out solvent thermal reaction at 130°C for 12h. After the reaction, cool naturally to room temperature, take out the MOF-grown nickel foam, and rinse it with distilled water and ethanol several times in turn to obtain a Ni-MOF nanosheet array grown on a nickel foam substrate. Figure 1 and attached Figure 2 (Figure a) are respectively the diffraction and scanning electron microscope images of Ni-MOF powder grown on the surface of nickel foam prepared in Example 1. It can be seen from the figure that the Ni-MOF nanosheets grow regularly on the surface of nickel foam, presenting the morphology of two-dimensional nanosheets.
[0028] (3) Weigh 0.03 g of ruthenium chloride and disperse it in 30 mL of ethanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 80 °C for 12 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Figure 1 and attached Figure 2 (Figure b) are the diffraction and scanning electron microscopy images of the self-supporting Ru / Ni-MOF powder prepared in Example 1. It can be seen from the accompanying figures that the introduction of atomically dispersed Ru does not change the original structure and morphology of Ni-MOF. Figure 3 This is an atomic force microscope image of the self-supporting Ru / Ni-MOF prepared in Example 1. It can be seen from the attached figure that the thickness of the Ru / Ni-MOF nanosheet is about 4nm. Figure 4This is a transmission electron microscopy image of the Ru / Ni-MOF prepared in Example 1. It can be seen from the figure that the elements C, O, Ru and Ni are evenly distributed on the surface of the nanosheet. Example 2
[0029] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0030] (2) Weigh 0.262g Ni(NO3)2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 24mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added. Solvothermal reaction was carried out at 130°C for 12h. After the reaction, it was cooled naturally to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain Ni-MOF nanosheet arrays grown on nickel foam substrate.
[0031] (3) Weigh 0.03 g of ruthenium chloride and disperse it in 30 mL of ethanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 80 °C for 12 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 3
[0032] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0033] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 30mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added. Solvothermal reaction was carried out at 130°C for 12h. After the reaction, it was cooled naturally to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain Ni-MOF nanosheet arrays grown on nickel foam substrate.
[0034] (3) Weigh 0.03 g of ruthenium chloride and disperse it in 30 mL of ethanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 80 °C for 12 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 4
[0035] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0036] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 30mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added. Solvothermal reaction was carried out at 130°C for 12h. After the reaction, it was cooled naturally to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain Ni-MOF nanosheet arrays grown on nickel foam substrate.
[0037] (3) Weigh 0.03 g of ruthenium chloride and disperse it in 30 mL of methanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 80 °C for 12 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 5
[0038] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0039] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 30mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added. Solvothermal reaction was carried out at 130°C for 12h. After the reaction, it was cooled naturally to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain Ni-MOF nanosheet arrays grown on nickel foam substrate.
[0040] (3) Weigh 0.04 g of ruthenium chloride and disperse it in 30 mL of ethanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 80 °C for 12 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 6
[0041] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 10 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0042] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 18mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added, and the solvent thermal reaction was carried out at a constant temperature of 160°C for 8h. After the reaction, it was naturally cooled to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain a Ni-MOF nanosheet array grown on the nickel foam substrate.
[0043] (3) Weigh 0.02 g of ruthenium chloride and disperse it in 40 mL of methanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor and heat it at 60 °C for 16 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 7
[0044] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 5 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0045] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 28mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution was placed in a 50mL reactor, and clean nickel foam was added. Solvothermal reaction was carried out at 110°C for 10h. After the reaction, it was cooled naturally to room temperature, and the nickel foam on which MOF was grown was taken out and rinsed with distilled water and ethanol several times in turn to obtain Ni-MOF nanosheet arrays grown on nickel foam substrate.
[0046] (3) Weigh 0.03 g of ruthenium chloride and disperse it in 20 mL of methanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 100 °C for 10 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 8
[0047] A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, the method comprising the following steps: (1) Place a 1.5 cm × 3.5 cm nickel foam in a 2M dilute hydrochloric acid solution, distilled water, and ethanol, respectively, and ultrasonically clean it for 8 minutes to remove the surface oxide layer and organic impurities. Dry it and set it aside.
[0048] (2) Weigh 0.214g NiCl2·6H2O and 0.24g 2,6-naphthalene dicarboxylic acid organic ligand and dissolve them in 20mL DMF and 3mL distilled water, and dissolve them by ultrasonic. The mixed solution is placed in a 50mL reactor, and clean nickel foam is added. Solvothermal reaction is carried out at 100°C for 16h. After the reaction, it is cooled naturally to room temperature, and the nickel foam on which MOF is grown is taken out and rinsed with distilled water and ethanol several times in turn to obtain a Ni-MOF nanosheet array grown on the nickel foam substrate.
[0049] (3) Weigh 0.04 g of ruthenium chloride and disperse it in 30 mL of ethanol. Stir for 10 min to form a uniform solution. Immerse the prepared Ni-MOF in the above solution and transfer it to a 50 mL reactor. Heat it at 70 °C for 14 h. Cool it naturally to room temperature and wash it with distilled water and ethanol several times to obtain a self-supporting Ru / Ni-MOF nanomaterial. Example 9
[0050] Application of the self-supporting Ru / Ni-MOF nanomaterial prepared in Example 1 above in water electrolysis.
[0051] Using a three-electrode system, the self-supporting Ru / Ni-MOF electrode prepared in Example 1 was directly used as the working electrode for hydrogen evolution reaction to carry out electrochemical performance testing. Figure 5 Linear voltammetry test shows that Ru / Ni-MOF has excellent electrocatalytic hydrogen evolution activity. Figure 6 This indicates that the catalyst has good long-term stability.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a self-supporting Ru / Ni-MOF electrocatalyst, characterized in that: The method comprises the following steps: Step 1, cutting and cleaning the nickel foam substrate; Step 2, dissolving the nickel salt and the carboxylic acid organic ligand in N,N-dimethylformamide DMF and distilled water under ultrasonic stirring conditions, placing the uniformly mixed solution in a high-pressure reactor, adding the cleaned and dried nickel foam in step 1, sealing and performing a solvent thermal reaction, reacting at a certain temperature for a set time, naturally cooling to room temperature, washing the taken-out nickel foam with distilled water and ethanol respectively, and freeze-drying to obtain a regular two-dimensional Ni-MOF nanosheet array grown on the nickel foam; Step 3, adding ruthenium chloride to an alcohol solvent, stirring thoroughly to form a uniform solution, then transferring the mixed solution to a reactor, and immersing the nickel foam growing Ni-MOF in the solution, heating at a constant temperature for ion exchange, and after the reaction, washing the self-supporting composite material with ethanol and distilled water for multiple times to obtain a Ru / Ni-MOF electrocatalyst.
2. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 1: the nickel foam is sequentially placed in a 2M dilute hydrochloric acid solution, distilled water and ethanol for ultrasonic cleaning for 5-10 minutes to remove the oxide layer and organic impurities on the surface.
3. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 2, the nickel salt is one of nickel chloride or nickel nitrate, and the organic ligand is 2,6-naphthalene dicarboxylic acid.
4. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 2, the molar ratio of nickel ions to organic ligands is 1:1-1:
3.
5. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 2, the volume ratio of DMF to distilled water is 6:1-10:
1.
6. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 2, the solvent thermal reaction temperature is 100-160° C. and the reaction time is 8-16 h.
7. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 3, the mass of ruthenium chloride is 0.02g-0.04g, and the volume of the alcohol solvent is 20-40mL; the alcohol solvent is one of methanol or ethanol.
8. The method for preparing the self-supporting Ru / Ni-MOF electrocatalyst according to claim 1, characterized in that: In step 3, the ion exchange reaction temperature is 60-100°C and the reaction time is 10-16h.
9. A self-supporting Ru / Ni-MOF electrocatalyst, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the self-supporting Ru / Ni-MOF electrocatalyst according to claim 9 in water electrolysis reaction.
Citation Information
Cited By
Self-supporting NiCu-MOF catalyst, preparation method and application of self-supporting NiCu-MOF catalyst in ammoxidation electrocatalysis
CN120272955A